2016
DOI: 10.1007/s40726-016-0039-z
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Disorders from Ambient (Urban) Air Pollution Emphasizing UFPM and PM2.5

Abstract: Exposure to ambient (urban) air pollution consisting of fine particles is linked with the increased risk of respiratory as well as cardiovascular diseases and cancers. Recent studies have, however, suggested the adverse effects of PM 2.5 and especially ultrafine particulate matter (UFPM or PM 0.1 : size <0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…Airborne PM were considered as one of the abiotic hazardous determinants for the development diseases such as cancer ( Quezada-Maldonado et al., 2018 ), respiratory ( Miller and Peden, 2014 ), cardiovascular ( Ulrich et al., 2002 ) and neurological disorders ( Bandyopadhyay, 2016 ; Crinnion, 2017 ; Genc et al., 2012 ; Loane et al., 2013 ; Xu et al., 2016 ). Presently, emergence of novel infectious microbial pathogens along with air pollution is one of severe threats to the human society globally.…”
Section: Discussionmentioning
confidence: 99%
“…Airborne PM were considered as one of the abiotic hazardous determinants for the development diseases such as cancer ( Quezada-Maldonado et al., 2018 ), respiratory ( Miller and Peden, 2014 ), cardiovascular ( Ulrich et al., 2002 ) and neurological disorders ( Bandyopadhyay, 2016 ; Crinnion, 2017 ; Genc et al., 2012 ; Loane et al., 2013 ; Xu et al., 2016 ). Presently, emergence of novel infectious microbial pathogens along with air pollution is one of severe threats to the human society globally.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond disruption of floral scents, diesel air pollution is more widely reported for its direct negative effects on mammalian health, including the cardiovascular system and the central nervous system (CNS) 12,13 . However, we understand very little about direct effects that diesel exhaust pollution has on insect health and behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…These studies examined the effects of a high dosage of particulate matter exposure, much higher than the concentrations of ambient PM 2.5 typically found in the United States. However, chronic exposure to even small doses of a pollutant may increase risk for neurodegeneration as individuals age (Bandyopadhyay 2016). Two recent U.S. studies with neuroimaging data on older adults found an association between living in areas with higher PM 2.5 concentrations and changes in brain structure, including white matter loss (Chen et al 2015) and reduced cerebral volume (Wilker et al 2015).…”
Section: Introductionmentioning
confidence: 99%